Preliminary survey on population density and structure of Saguinus tripartitus Milne-Eduards from the Peruvian Amazon - Aquino, Rolando (2005)
Censuses by transects were carried out in January of the 2005 in the Aushiri river basin to determine the population density and population structure of the «golden-mantle tamarin» (Saguinus tripartitus MilneEduards). We recorded 17 groups and population density was calculated in 13,5 individuals/km2 . The size of the groups varied from four to eight individuals, with an average size of 5,3 individuals per group. The basic composition of a group was that of a reproductive pair with progeny of two to six individuals. The adults represented 75% of the total population.